THE IMPACT OF INFLATION ON ECONOMIC GROWTH (CASE STUDY IN INDONESIA 1987-2016) - Yulianto, Fariz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Economic growth is a key in developing a country. The amount of how much economic growth can develop a country can be seen in how it affects everything starting from the amount of supply in a country. Economic growth also showed the extent to which economic activity will affect additional income of the people within a given period. Economic growth can be interpreted as a process that the changes felt in the long term and it can be measured by using GDP growth or in this case the change in total output.Â Another reason why economic growth is important is that since it is affected by GDP growth, then every time there is an increase in total output, that means the economic growth increased and so will the prosperity of the country. However, Economic Growth does not get affected by only the GDP growth, but also other factors like inflation. This research aims to analyse the impact of inflation towards economic growth in a given period of time, and in this research, the period will be starting from 1987 until 2016.This research uses Ordinary Least Square or OLS to determine the effect of independent variables on the dependent variable. The results obtained in this research indicate that inflation affect economic growthKeywords: Economic growth, inflation, GDP growth.